PURIFICATION AND CHARACTERIZATION OF Aeromonas media KLU 11.16 CHITOSANASE ISOLATED FROM SHRIMP WASTE - Ekowati Chasanah; Gintung Patantis; Dewi Seswita Zilda; Mahrus Ali; Yenny Risjani (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Our previous study found that KLU 11.16, isolated from shrimp waste secreted chitinolytic enzymes. The crude enzyme was interesting since their chitooligosccharide was able to inhibit some pathogenic bacteria. In this study we report a purification and characterization of the chitosanase enzyme produced and the identification of the KLU 11.16. Purification of the enzyme was done two steps by ion exchange chromatography followed by gel filtration. Two out of 4 peaks from Gel Filtration step, i.e. fraction 16 and 33 were capable of hydrolyzing 100% deacetylated chitosan, indicating that both fractions contained chitosanase enzyme. The enzyme from fraction 16 had approximate molecular weight of 98.3 kDa. The enzyme worked optimally at temperature of 300C, and pH 6. Addition of Ca2+, Fe2+, K+, Na+ ions in the form of Cl2 salt and detergent Triton X-100 increased the enzyme activity, while Co2+, Mn2+ and Zn2+ ions in the same concentration decreased the enzyme acitivity. Addition of EDTA and SDS significantly decreased the enzyme activity. Molecular based identification revealed that KLU 11.16 was 99% similar to Aeromonas media.